Analisis Kecerdasan Naturalis Siswa Sekolah Dasar dalam Pembelajaran Tematik - Supeno Supeno; Siswanto Siswanto (Universitas Negeri Makassar, 2022)
This study aims to describe the naturalist intelligence of elementary school students in thematic learning. The research method used is descriptive qualitative research method, with preparatory/pre-field steps, field work, and data analysis. The data sources that are the key people are all students of class VI SDN 010 Bangun Purba, totaling 14 students consisting of 7 male students and 7 female students. Data collection techniques used are documentation, observation, and interviews. The research instruments used were student observation sheets, teacher observation sheets, and interview guidelines. The data analysis technique was carried out using qualitative data analysis techniques. The results showed that students' naturalist intelligence was in the high category. The naturalist intelligence of male students is lower than the naturalist intelligence of female students. The conclusion of this study is that the naturalist intelligence of students is high because students are very observant with thematic learning carried out by the teacher. Teachers who apply thematic learning in elementary schools really implement their thematic learning very well so that students' naturalist intelligence can be achieved at the highest level. Further research is needed on other intelligences that can be achieved through the application of thematic learning in elementary schools, considering that students have 8 kinds of intelligence.